Lang ren chuan shuo - Xie Le; BOB (X tan xian te gong dui, 2010)
The X-Venture Xplorers find themselves in 18th century France to investigate the mystery of the werewolf! Sure, science back then wasn’t as advanced as it is now, but surely not all the reports the team has been getting can be false – can they? Now the X-Venture Xplorers find themselves racing against time for their lives, ‘cos when it comes to werewolves, their bite is definitely worse than their bark! In the end, there is only one question, and one answer – Werewolf? There wolf! Read on, and have a howling good time!